ELECTROMAGNETIC RADIATION OF EXTREMELY LOW FREQUENCY (ELF) - Septiana Kurniasari; Mursalin Mursalin; Kisman R. Akuba; Devi Triana Paputungan; Rila Virna; Muhammad Yunus (Universitas Bhinneka PGRI, 2024)
The spectrum emitted by electromagnetic wave radiation has various frequencies, one of which is Extremely Low Frequency (ELF), and is often found in educational environments, originating from various electronic devices, high voltage electrical panels, and internet network supporting devices. Based on this description, it is necessary to measure ELF electromagnetic radiation in the Faculty of Mathematics and Natural Sciences environment at Universitas Negeri Gorontalo. This research was carried out by measuring magnetic field values (µT) at 42 location points using a Portable Electromagnetic Field Tester (EMF Tester). The research results show that all of these location points are within the safe threshold based on ICNIRP and WHO regulations, namely below 200 µT, with the highest ELF magnetic field value is 2.81 µT, and the lowest ELF magnetic field value is 0.003 µT. However, there are several studies showing that exposure to ELF electromagnetic field radiation can produce free radicals, causing cell damage. The results of this research can be used as a basis for making health policies for the Faculty of Mathematics and Natural Sciences academic community at Universitas Negeri Gorontalo.